1974
DOI: 10.1161/01.res.35.2.184
|View full text |Cite
|
Sign up to set email alerts
|

A Model of Cardiac Muscle Dynamics

Abstract: A mathematical model is presented describing the time-and length-dependent behavior of cardiac muscle. The model describes a wider variety of experimental data than do previously published models. It incorporates a modification of the Hill equation describing the force-velocity relation. Based on the sliding filament theory, the revised equation includes the effects of finite cross-bridge compliance proposed by A. F. Huxley. The essential simplicity of the Hill equation is retained; however, the model successf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Subsequent trials revealed that at the reduced length, the construct has a much lower linear passive stiffness and retains some prestress even at low initial stretch. These results indicate that the stiffness which appeared linear at the original length is actually part of an exponential or partially nonlinear stiffness function common in biological tissues [11;26]. …”
Section: Discussionmentioning
confidence: 99%
“…Subsequent trials revealed that at the reduced length, the construct has a much lower linear passive stiffness and retains some prestress even at low initial stretch. These results indicate that the stiffness which appeared linear at the original length is actually part of an exponential or partially nonlinear stiffness function common in biological tissues [11;26]. …”
Section: Discussionmentioning
confidence: 99%
“…The isolated papillary muscle, ventricular strips, and Purkinje fiber preparations have proven to be critical in understanding the passive and active electromechanical properties of cardiac tissue [27;28]. Full mechanical characterization of the passive and active elastomechanics of a single, end-supported cardiomyocyte can be accomplished using optical sensing and mechanical feedback control [29], albeit with rather expensive hardware (IonOptix, Westwood, MA, USA).…”
Section: Introductionmentioning
confidence: 99%
“…HilTs mathematical expression for the contraction velocity of the contractile element under dif f erent loads has been expanded to simulate heart-muscle by addition of a time-dependent »active state« and lengthdependent factors, reflecting the dependence of the actively developed force on muscle-length, in the studies of Grood et al [9] and Fung [7). Examination of heart-muscle dynamics showed that five properties are most relevant: the influence of diastolic pressure on the filling-volume, the dependence of ejection-volume on the presystolic The Hill-model contains a contractile element (CE), which represents the force-velocity relations, and a series elastic element (SE) which is used in explaining muscle reaction during rapid length-changes.…”
Section: Introductionmentioning
confidence: 99%
“…Grood [9], going on this assumption, f urther hypothesized that the parallel elastic element is only stressed at high muscle-lengths and arrived at a muscle model shown in Fig. Grood [9], going on this assumption, f urther hypothesized that the parallel elastic element is only stressed at high muscle-lengths and arrived at a muscle model shown in Fig.…”
Section: Introductionmentioning
confidence: 99%